Marketing Syariah sebagai Alternatif Pemasaran Berkelanjutan di Era Digital - Helisia Krisdayanti; Fakhrina; Amirah Andika Rifdayanti; Safira Elfadhilah (Indo Publishing, 2025)
Islamic marketing as an alternative approach to sustainable marketing in the digital era offers a framework that not only prioritizes profit but also emphasizes ethical values, justice, and long-term sustainability in every business activity. Within the context of digital transformation, Islamic marketing leverages technologies such as social media, e-commerce, and digital analytics to expand market reach while upholding principles of honesty, transparency, and the prohibition of consumer manipulation. This approach builds long-term trust between businesses and consumers by prioritizing satisfaction, safety, and sustainability. Moreover, Islamic marketing provides solutions to digital-era challenges—such as intense competition and information overload—by delivering marketing messages that are authentic, responsible, and aligned with modern moral values. The application of principles such as value-based marketing, fairness in transactions, and commitment to environmental sustainability strengthens its relevance and adaptability to changing consumer behavior. Thus, Islamic marketing serves not only as an ethical alternative but also as an effective and strategic model to enhance business competitiveness in a dynamic digital landscape, while supporting the realization of truly sustainable marketing practices.